80 Psychological risk assessment – bridging the research-practitioner gap. (24th April 2018) - Schneider, I; Mädler, M; Clos, C; Lang, J
Abstract : Introduction: Due to the consequences of globalisation and digitalization on working conditions, psychological risk factors at work rise in importance. Prevention strategies for designing working conditions that maintain mental health and work functioning are needed. Only few companies worldwide have implemented psychological risk management regularly. One reason might be the lack of suitable measurement tools. Although, many researchers developed reliable assessment instruments for psychosocial stress at work, most of them fail in helping redesigning working conditions on the technical or organisational level. With the help of existing measurements mainly personal prevention actions are possible. Therefore an instrument is needed that measures the objective work factor and not the subjective stress of the employees. The aim of this investigation is to develop and validate a practical online assessment of psychological risk at work according to scientific standards. Methods: From November 2015 to March 2016, psychological work factors that have impact on mental health were determined by means of literature searches, workshops and telephone interviews with experts. An online assessment was developed between April 2016 and September 2016. From October 2016 to March 2017 risk analyses were carried out by experts and employees on the basis of 10 pilot companies from the public sector (about 2000 respondents). Results: The online assessment provides statements on the work content, work organisation, social relations and the work environment. With 48 items, psychological work factors with regard to the task (not the person) are recorded with value-neutral formulations. The response scale is a 4-step frequency scale. First analyses prove the objectivity, reliability and validity of the instrument. Conclusion: The online assessment contains psychological work factors that can be generalised to any work tasks. It might be used across all sectors. The instrument measures psychological risk at work economically and largely independent of the individual response.